2012
DOI: 10.3233/jad-2012-112090
|View full text |Cite
|
Sign up to set email alerts
|

Brain Pericytes ABCA1 Expression Mediates Cholesterol Efflux but not Cellular Amyloid-β Peptide Accumulation

Abstract: In brain, excess cholesterol is metabolized into 24S-hydroxycholesterol (24S-OH-chol) and eliminated into the circulation across the blood-brain barrier. 24S-OH-chol is a natural agonist of the nuclear liver X receptors (LXRs) involved in peripheral cholesterol homeostasis. The effects of this oxysterol on the pericytes embedded in the basal lamina of this barrier (close to the brain compartment) have not been previously studied. We used primary cultures of brain pericytes to demonstrate that the latter expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
68
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 61 publications
11
68
0
1
Order By: Relevance
“…In the brain, excess cholesterol is metabolized into 24S-hydroxycholesterol (24S-OH-chol), which is an endogenous ligand for LXR. 97 Shimizu et al demonstrated that the GDNF, secreted from the brain and peripheral nerve pericytes, is one of the key molecules responsible for the up-regulation of claudin-5 expression and the permeability in the BBB. 98 Furthermore, pericytes are able to internalize the amyloid-b peptides, which accumulate in brain of Alzheimer's disease patients.…”
Section: Astrocytesmentioning
confidence: 99%
“…In the brain, excess cholesterol is metabolized into 24S-hydroxycholesterol (24S-OH-chol), which is an endogenous ligand for LXR. 97 Shimizu et al demonstrated that the GDNF, secreted from the brain and peripheral nerve pericytes, is one of the key molecules responsible for the up-regulation of claudin-5 expression and the permeability in the BBB. 98 Furthermore, pericytes are able to internalize the amyloid-b peptides, which accumulate in brain of Alzheimer's disease patients.…”
Section: Astrocytesmentioning
confidence: 99%
“…This finding was supported by in vitro studies demonstrating ABCA1 significant role in the regulation of neuronal cholesterol efflux to apoE and in suppression of APP processing to generate Aβ peptides, 92,94 contradicting those reported by Fukumoto et al 106 Furthermore, results from in vitro studies performed in pericytes demonstrated that treatment of primary pericytes culture with 24S-OH-cholesterol, a cholesterol metabolite and a natural agonist of LXR, increased expression of ABCA1, and such an increase in ABCA1 expression correlated with cholesterol transfer to apoE, apoA-I, and HDL particles, the key players in brain cholesterol homeostasis and amyloid accumulation and deposition, and its inhibition decreased this efflux. 73 Yet the increase in ABCA1 expression was not associated with any change in Aβ 40 and Aβ 42 peptide accumulation inside pericytes. 73 Besides, in vitro inhibition studies supported the role of ABCA1 in Aβ production.…”
mentioning
confidence: 99%
“…73 Yet the increase in ABCA1 expression was not associated with any change in Aβ 40 and Aβ 42 peptide accumulation inside pericytes. 73 Besides, in vitro inhibition studies supported the role of ABCA1 in Aβ production. Recently, in their in vitro study, Kim et al demonstrated using the mouse neuroblastoma N2a cells that suppression of ABCA1 expression by miR-106b impaired cellular cholesterol efflux and increased the levels of secreted Aβ.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ce type cellulaire, connu depuis plus de 150 ans, semble essentiel à la physiologie ainsi qu'au maintien de l'intégrité de la BHE [9]. Cependant, peu de données sont disponibles concernant ces cellules et leur rôle précis, notamment dans la régulation de l'homéostasie cérébrale du cholestérol (probablement perturbée dans le cerveau des patients atteints de MA), reste encore peu exploré [10]. L'équipe de B. Zlokovic a ainsi démontré que la régulation de brale, les relations entre les produits de ce gène et la BHE restent cependant très peu étudiées.…”
unclassified